Learning With AI: The Impact of ChatGPT and QuillBot to Approaches to Learning (ATL) Skills of Students - Gaboy, Regidor G.; Delos Santos, Ma. Ruby Hiyasmin M.; Collantes, Leila M.; Juntarciego, Mary Joy Cabreza (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to determine the experiences and perspectives of students of Second Language English (ESL) or English as Foreign Language (EFL) Year 2 International Baccalaureate Diploma Programme (IB DP), on how Artificial Intelligence - powered assisted tools impact their Approaches to Learning (ATL) skills. Methodology: This study adopted a narrative approach, an appropriate theoretical basis with Braun and Clarke's Thematic Analysis for qualitative data to uncover codes, sub themes and themes. The method used to gather data was a face-to-face Focus Group Discussion (FGD) with thirteen Year 2 IB DP students (Grade 12) participants. The FGD was recorded and transcribed. Main Findings: The use of Artificial Intelligence tools had positive impact to a lesser extent and temporarily helpful on their thinking, research and writing skills, with highly positive effect to self-management skills but detrimental in the long term. Overall, AI tools can cause adverse effects on the users, but if it is properly integrated and correctly use with appropriate guidelines, AI tools have the potential to be beneficial for learners. Novelty/Originality of this study: This study explores the impact of specific AI tools, ChatGPT and QuillBot, on the Approaches to Learning skills of students at an IB world school. This study focused on writing, thinking, research, and self-management skills from the perspective of students, themselves, hence, offering insights how AI tools enhance or degrade skills that could shape future educational policies.